A Comparative Study of Flat Slab and Waffle Slab Structure for Efficiency of Convention Building Slab System - Efendi, Efendi; Irfan Rifai, Andri; Savitri, Amanatullah (Civil Infrastructure Engineering and Architectural Design, 2025)
In the world of construction, aesthetic has become an important factor that must be considered. The aesthetic elements consist of wholeness, prominence and balance. However, aesthetic values can be influenced by several factors, namely economic, social, cultural, technological, ergonomic and psychological factors and this cause that in commercial development or the building that use slab system for foundation is used greatly affects it in terms of aesthetics and also cost effectiveness. The author's purpose of doing this research is to analyse the efficiency of volume in concrete and deflection between Flat Slab system and Waffle slab system. This research uses a case study at the Pasir Putih Convention, Batam, Indonesia. The analysis is done with ETABS software based on the local standards or known as Indonesia National Standard (abbreviated SNI). The choice of a slab system in a development is very important, especially if the building or construction is categorized as commercial structure. Based on the data obtained by researchers in terms of economics and deflection, Waffle Slab System is the right choice, meanwhile in terms of ease construction Waffle Slab System will be the secondary choice than Flat Slab, Since Flat Slab is more ease of framework installation than Waffle Slab.